2020
DOI: 10.1016/j.ejmech.2020.112849
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating pretomanid analogues for Chagas disease: Hit-to-lead studies reveal both in vitro and in vivo trypanocidal efficacy

Abstract: Phenotypic screening of a 900 compound library of antitubercular nitroimidazole derivatives related to pretomanid against the protozoan parasite Trypanosoma cruzi (the causative agent for Chagas disease) identified several structurally diverse hits with an unknown mode of action. Following initial profiling, a first proof-of-concept in vivo study was undertaken, in which once daily oral dosing of a 7-substituted 2-nitroimidazooxazine analogue suppressed blood parasitemia to low or undetectable levels, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
(140 reference statements)
1
14
0
1
Order By: Relevance
“…These compounds completely cleared parasites (100%) from 3T3 host cells at E max concentrations (maximal activity achievable in dose-response curves, Fig 6), in contrast to the CYP51 inhibitor, posaconazole that showed 87% inhibition at E max . This phenotypic characteristic suggested that MCC9481 and MCC9482 might not inhibit the CYP enzyme, consistent with other bicyclic nitroimidazole analogs that were reported to be inactive against CYP51 [21].…”
Section: Antitrypanosomal Activity Of Extended Side Chains Of Nitroim...supporting
confidence: 83%
See 2 more Smart Citations
“…These compounds completely cleared parasites (100%) from 3T3 host cells at E max concentrations (maximal activity achievable in dose-response curves, Fig 6), in contrast to the CYP51 inhibitor, posaconazole that showed 87% inhibition at E max . This phenotypic characteristic suggested that MCC9481 and MCC9482 might not inhibit the CYP enzyme, consistent with other bicyclic nitroimidazole analogs that were reported to be inactive against CYP51 [21].…”
Section: Antitrypanosomal Activity Of Extended Side Chains Of Nitroim...supporting
confidence: 83%
“…The repurposing potential of delamanid and pretomanid analogs for the treatment of kinetoplastid diseases [18, 20, 21] led us to investigate the antitrypansomal activity of nitroimidazopyrazinones against T. cruzi . Initial investigations using high content imaging demonstrated that analogs with extended biaryl side chains were highly active against T. cruzi (IC 50 = 0.016–4.2 µM) [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Vermelho et al, it is a disease considered neglected and few drugs are being developed for the treatment of CD with no progress in this direction since the 1960s [6]. Regarding the discovery of new drugs for CD, the strategy of target-based drug discovery was hampered by the lack of targets well validated [7]. According to Pérez-Molina and Molina, in the area of drug development, existing animal models are limited because they have a poor translation of in vivo data [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to the authors, it is necessary to standardize new animal models capable of more safely predicting the effectiveness of new drug candidates [8]. According to Thompson et al, the phenotypic screening of libraries with several compounds is still considered the best strategy to identify new leads or starting points [7]. Moreover, the discovery of new drugs for Chagas disease need collaborative networks involving academia, pharmaceutical companies, government organs and entities such as DNDi (Drugs for Neglected Diseases initiative), all of them contributing for substantial advances where actions must be as synergistic as possible in order to support the translation of academic research into available drugs [9,10].…”
Section: Introductionmentioning
confidence: 99%